Huma man Tiss ssue Kallikreins – A Famil ily with ma many surprises - Tove I. Klokk (De Gruyter, 2006)
The hu human tissue kallikreins (KLKs) form a family of 15 closely related serine proteases. They are encoded by conserved genes tandemly located in a large gene clu luster (320 kb) on chromosome 19q13.4. The first three members of the family, KLK1 (tissue kallikrein), KLK2, and KLK3 (Prostate specific antigen, PSA) were long thought ht to be the only members of the family. However, during the last decade the availability of hu human genome sequence and extensive screening of the KLK locus has revealed the presence of 12 additional KLK genes. With the complete descrip iption of the hu human KLK locus, the main research effort is now centered around the elucidation of potential biological functions of the KLKs. PSA/KLK3 is a well known biomarker for prostate cancer; KLK2 is also being considered as a marker for this disease. e. At present, other members of the KLK family are under investigation as potential markers in disease states. In fact, several have shown potential as prognostic biomarkers, especially in hormone dependent cancers, suchas those involving the prostate, breast and ovary. Although the biological function of KLKs are still in large part unknown, they are expressed in a wide range of tissues, suggesting a functional role in diverse physiological and pathophysiological processes. Among others, these inclu lude skin desquamation and other skin diseases,tooth development and enamel defects, Alzheimer’s disease, and Parkinson’s disease. e. An increasing interest in the role of KLKs in disease has also resulted in research into potential substrates of the KLKs, which may give clues to theirfunctional role. e. In vitro studies have shown that some KLKs can auto-activate, while others can activate each other, suggesting that the KLKs may be part of an enzymatic cascade. e. Further research will reveal the functional roles of KLKs in various tissues, and whether they have clinical utility as biomarkers for disease states, a , and p d possibly a y also a o as t s therapeutic t c targets.